ANALISIS STANDAR OPERASIONAL PROSEDUR UNIT TERMINAL SERVICE OFFICER DALAM PELAKSANAAN DELAY SERVICE DI TERMINAL DOMESTIK BANDAR UDARA INTERNASIONAL I GUSTI NGURAH RAI, BALI - Dary Riliandra, Priambudi; Fauziah, Syifa (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
I Gusti Ngurah Rai Airport in Denpasar, Bali, is one of the busiest airports in Indonesia. The high volume of passengers has the potential to cause issues such as flight delays. Handling these delays requires serious attention, which falls under the responsibility of various airport units, one of which is the terminal service officer (TSO) unit. This research aims to analyze the standard operating procedures (SOP) implemented by the TSO unit in handling delays at the domestic terminal of I Gusti Ngurah Rai Airport by understanding the existing SOPs. This research employs a descriptive qualitative approach. The data used includes both primary and secondary data. Primary data is obtained from observations and interviews, while secondary data comes from SOPs, photos, and regulations related to the issues being studied. The data analysis techniques used are data collection, data reduction, data presentation, and conclusion drawing. To test the validity of the data, triangulation techniques are used.